REAKSI SAHAM INDEKS JII TERHADAP PENGUMUMAN RESHUFFLE KABINET KERJA TAHUN 2015 DI BURSA EFEK INDONESIA - Arviani, Herizka Ayuk; Khoirunnisa, Rikha Muftia (Universitas Ahmad Dahlan, 2017)
This study aims to determine the speed of JII stock price reaction on the Indonesia Stock Exchange around the date of the announcement of the Working Cabinet reshuffle and to analyze the difference in average trade volume in the period before and after the announcement of the Working Cabinet reshuffle. This data collection technique uses population techniques taken by 30 companies in the JII Index for the period June - November 2015 with observation period 10 days before and 10 days after the announcement. Analysis tools that are used to determine the reaction of stock prices before and after using one sample t test while the analytical tool to distinguish the average trading volume using paired sample t test using an alpha level (Î±) of 10%. The results of the analysis of stock price reactions indicate that there is a JII stock price reaction at Indonesia Stock Exchange in the period before and after the announcement of the Working Cabinet reshuffle. Because abnormal returns occur at H-7, H-4, H-1, H0, H + 1, H + 7 and H + 10. And the results of the average volume test that is there is a difference in the average trading volume before and after the announcement of the Working Cabinet reshuffle. This can be seen from the significance value lower than alpha 10% (0.033 <0.0.1).